ARTIFICIAL INTELLIGENCE ITS IMPORTANCE IN HUMAN LIFE AND ACTIVITY (Web of Technology: Multidimensional Research Journal, 2024)
This article talks about the importance of artificial intelligence in our daily life, how it affects us and its benefits, its various functions and its benefits in education.